Fecal Capsule as a Therapeutic Strategy in IgA Nephropathy: A Brief Report - Zhi, Wenqiang; Song, Wenzhu; Abdi Saed, Yasin; Wang, Yi; Li, Yafeng (Frontiers in Medicine, 2022)
In this brief report, we reported an IgA nephropathy (IgAN) patient who presented in November 2020 with an acute exacerbation with massive proteinuria and diarrhea. He had the earliest onset in 2018 when his IgAN was diagnosed by renal biopsy. He has been treated with active ACEI / ARB drugs for more than 90 days, intermittent steroid therapy, combined with anti-infective therapy. Although his acute symptoms resolved with each episode, he became increasingly severe as the interval between episodes shortened. Accordingly, the immunosuppressive drugs were administered under the KDIGO guidelines and related guidelines. However,the patient and his family refused this treatment. We pondered over the possible pathogenesis of IgAN, and after a full discussion with the patient and his family, FMT was administered to him after obtaining his informed consent. During the FMT procedure, one healthy volunteer (the doctor himself) also took the FMT capsules. In the end, the patient’s urine protein dropped significantly and even turned negative after treatment. Neither the patient nor the healthy volunteer experienced any serious adverse effects during the use of the capsules and the subsequent six-month follow-up period. We also used metagenomic sequencing to analyze the intestinal flora of patients before and after treatment, and a gradual increase stood out in the abundance of the patient’s intestinal flora after drug administration.